Are sigma modulators an effective opportunity for cancer treatment? A patent overview (1996-2016). (4th May 2017) - Collina, Simona; Bignardi, Emanuele; Rui, Marta; Rossi, Daniela; Gaggeri, Raffaella; Zamagni, Alice; Cortesi, Michela; Tesei, Anna
ABSTRACT: Introduction: Although several molecular targets against cancer have been identified, there is a continuous need for new therapeutic strategies. Sigma Receptors (SRs) overexpression has been recently associated with different cancer conditions. Therefore, novel anticancer agents targeting SRs may increase the specificity of therapies, overcoming some of the common drawbacks of conventional chemotherapy. Areas covered: The present review focuses on patent documents disclosing SR modulators with possible application in cancer therapy and diagnosis. The analysis reviews patents of the last two decades (1996–2016); patents were grouped according to target subtypes (S1R, S2R, pan-SRs) and relevant Applicants. The literature was searched through Espacenet, ISI Web, PatentScope and PubMed databases. Expert opinion: The number of patents related to SRs and cancer has increased in the last twenty years, confirming the importance of this receptor family as valuable target against neoplasias. Despite their short history in the cancer scenario, many SR modulators are at pre-clinical stage and one is undergoing a phase II clinical trial. SRs ligands may represent a powerful source of innovative antitumor therapeutics. Further investigation is needed for validating SR modulators as anti-cancer drugs. We strongly hope that this review could stimulate the interest of both Academia and pharmaceutical companies.